2015
DOI: 10.1007/s00223-015-0007-4
|View full text |Cite
|
Sign up to set email alerts
|

Teriparatide Therapy Reduces Serum Phosphate and Intima-Media Thickness at the Carotid Wall Artery in Patients with Osteoporosis

Abstract: Although cross-sectional and longitudinal studies report a relationship between osteoporosis and cardiovascular disorders (known as the bone-cardiovascular axis), the benefits of osteoporosis treatment on atherosclerosis are largely unclear. Teriparatide is a bone-forming agent that increases urinary phosphate excretion. Because elevated serum phosphate is associated with the development of atherosclerosis, the purpose of our study was to examine the relationship among lumbar spine bone mineral density (LS-BMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
3
8
0
1
Order By: Relevance
“…In rats with induced myocardial infarction PTH application led to mobilization of angiogenic progenitor cells from bone marrow and improved survival and reduced infarct size compared to sham treatment, probably via promoting VEGF-mediated cardiac neovascularization [34]. Also in humans, PTH administration was associated with increases in circulating hematopoietic stem cells and an improvement in carotid intima-media thickness [35, 36]. Patients with pHPT exhibited higher numbers of circulating bone marrow derived progenitor cells compared to healthy controls, and increased VEGF levels [37].…”
Section: Discussionmentioning
confidence: 99%
“…In rats with induced myocardial infarction PTH application led to mobilization of angiogenic progenitor cells from bone marrow and improved survival and reduced infarct size compared to sham treatment, probably via promoting VEGF-mediated cardiac neovascularization [34]. Also in humans, PTH administration was associated with increases in circulating hematopoietic stem cells and an improvement in carotid intima-media thickness [35, 36]. Patients with pHPT exhibited higher numbers of circulating bone marrow derived progenitor cells compared to healthy controls, and increased VEGF levels [37].…”
Section: Discussionmentioning
confidence: 99%
“…31 Baykan et al 32 reported a significant decrease in FMD % in 21 patients with primary hyperparathyroidism compared to control group. Yoda et al 33 observed a decrease in LDL and increase in HDL levels in 28 osteoporotic patients treated with teriparatide for 12 months period. In the present study, we evaluated the effects of intermittent teriparatide treatment for 6 months on endothelial function assessed by ultrasonography and on biochemical markers for inflammation and atherosclerosis in postmenopausal osteoporosis patients.…”
Section: Discussionmentioning
confidence: 97%
“…reported a significant decrease in FMD% in 21 patients with primary hyperparathyroidism compared to control group. Yoda et al . observed a decrease in LDL and increase in HDL levels in 28 osteoporotic patients treated with teriparatide for 12 months period.…”
Section: Discussionmentioning
confidence: 98%
“…Также авторы отметили снижение уровня фосфата сыворотки уже через 1 мес после первого введения терипаратида, которое прямо коррелировало с изменением толщины КИМ сонных артерий к концу курса терапии (r=0,431, р=0,025). Авторы предполагают, что уменьшение толщины КИМ может быть частично обусловлено снижением сывороточного фосфата, оказывающего «токсический» эффект на сосудистую стенку [38].…”
Section: терипаратидunclassified